Ok so in 20/42 video dp=0=dx/A(x,y)+dy/B(x,y) thus should dx/A(x,y) = -dy/B(x,y) thus dx/X = dy/2y Since -(dy/-2y) Thanks for your time. i love how f(p) is litraly the constant haha thats makes everything very clear and nice.
@daniwinckler53544 жыл бұрын
In the previous video you had the form dx/A(x,y) + dy/B(x,y) = 0 but in this video you have dx/A(x,y) = dy/B(x,y) which means that you have changed the sign of the dy/B(x,y) term. Should it be written as the first or the second definition?
@MichelvanBiezen4 жыл бұрын
In this video we have A(x,y) = dx and B(x,y) = dy therefore A(x,y)/dx = B(x,y)/dy
@jason16825 жыл бұрын
isn't it y^-1 instead of y^1 from the Equation in previous video lecture
@curtpiazza1688 Жыл бұрын
😊
@MichelvanBiezen Жыл бұрын
🙂
@PaulQuelet6 жыл бұрын
This is the exact same as the previous video. Double upload.
@MichelvanBiezen6 жыл бұрын
These are different parts of the same problem. (thanks for bringing it to our attention)